Student obesity prevalence and behavioral outcomes for the massachusetts childhood obesity research demonstration project. Issue 7 (July 2017) - Franckle, Rebecca L.; Falbe, Jennifer; Gortmaker, Steven; Barrett, Jessica L.; Giles, Catherine; Ganter, Claudia; Blaine, Rachel E.; Buszkiewicz, James; Taveras, Elsie M.; Kwass, Jo‐Ann; Land, Thomas; Davison, Kirsten K.
Abstract : Objective: To examine changes in prevalence of obesity and target health behaviors (fruit, vegetable, and beverage consumption; physical activity; screen time; sleep duration) among students from communities that participated in the Massachusetts Childhood Obesity Research Demonstration (MA‐CORD) project compared to controls. Methods: MA‐CORD was implemented in two low‐income communities. School‐level prevalence of obesity among students in first, fourth, and seventh grades was calculated for the intervention communities and nine matched control communities pre and post intervention. Fourth‐ and seventh‐grade students' self‐reported health behaviors were measured in intervention communities at baseline and post intervention. Results: Among seventh‐graders (the student group with greatest intervention exposure), a statistically significant decrease in prevalence of obesity from baseline to post intervention in Community 2 ( − 2.68%, P  = 0.049) and a similar but nonsignificant decrease in Community 1 ( − 2.24%, P  = 0.099) was observed. Fourth‐ and seventh‐grade students in both communities were more likely to meet behavioral targets post intervention for sugar‐sweetened beverages (both communities: P  < 0.0001) and water (Community 1: P  < 0.01; Community 2: P  = 0.04) and in Community 2 for screen time ( P  < 0.01). Conclusions: This multisector intervention was associated with a modest reduction in obesity prevalence among seventh‐graders in one community compared to controls, along with improvements in behavioral targets.